IMPACT OF INTERNAL CORPORATE GOVERNANCE MECHANISMS ON THE FINANCIAL AND ENVIRONMENTAL PERFORMANCE OF BANKS IN UAE DURING THE COVID-19 PANDEMIC - Mohammed Almashhadani (Transpublika Publisher, 2023)
The COVID-19 pandemic has presented new challenges, leading to increased scrutiny of the financial resilience and sustainability of the banking industry. This conceptual investigation delves into the intricate relationships between internal corporate governance measures, such as ownership concentration and capital intensity, and the financial and environmental performance of banks in the United Arab Emirates (UAE) during the pandemic. By examining the unique dynamics of the UAE's banking sector in response to the crisis, this research aims to advance our theoretical understanding of how internal corporate governance systems influence financial and environmental performance during periods of turmoil. This study addresses a critical gap in the literature by exploring the underexplored link between internal corporate governance practices and financial as well as environmental performance in the context of an international financial crisis. It illuminates how specific governance structures impact the decision-making processes of UAE banks, ultimately affecting their financial and environmental outcomes. Drawing on theoretical frameworks rooted in agency theory, stakeholder theory, and corporate social responsibility, this research leverages the uncertainties brought about by the pandemic to test and validate these theories in a rapidly evolving economic landscape. Employing a mixed-methods approach that combines quantitative financial data analysis with qualitative insights from key stakeholders in the UAE's banking sector, this research provides a comprehensive evaluation, encompassing both qualitative and quantitative findings, which may reshape our understanding of how internal corporate governance systems impact financial and environmental performance.